The Mode of Constructing Safe Trajectories of Motion of the Unmanned Aerial Vehicle while Monitoring Power Lines Considering the Influence of their Electromagnetic Fields - Shabanova A.R.; Tolstoy I.M.; Lebedev I.V. (Problems of the Regional Energetics, 2019)
The aim of this paper is to increase the flight safety of an unmanned aerial vehicle that monitors power lines under the negative influence of electromagnetic fields on the on-board equipment. This problem was solved with algorithms for photo- and video-imaging and determination of wire sag. The development of monitoring algorithms should overcome the limitations of the ex-isting solutions. Particularly, various systems employ suboptimal routes of aerial vehicle, as well introduce non-universal constraints of flight zone. Besides, the considered approaches do not account for peculiarities of aerial imaging and for structural specifics of power line elements. This leads to poorer image processing performance and causes additional errors. To improve evaluation of power line characteristics, the algorithm of aerial imaging is proposed, which in-cludes vehicle position adjustment relative to wire for two imaging settings. To ensure safe per-formance of onboard hardware, a calculation methodology for electromagnetic field distribution is presented, which allows determine the minimum distance between the wire and the vehicle. Experimental results, obtained in simulator, show 90.22% accuracy of the proposed method. The most important research outcomes consist in achieved refinement of aerial imaging in over-head power line monitoring, as well in automation of wire sag calculation based on image data. The scientific relevance of the research consists in potential improvement of fault-tolerance of power transmission networks and decrease of power losses because of early recognition of power line failures and due repair. Consequently, maintenance costs of overhead power line service can be optimized.